Respuestas
Respuesta dada por:
1
Respuesta:
Caso 1
base(b) = 8
altura(h) = 6
Caso 2
base(b) = 6
altura(h) = 8
Explicación paso a paso:
A = b * h
P = 2b + 2h
P = 2(b + h)
28 = 2(b + h)
14 = b+ h
b + h = 14
b = 14 - h
A = b * h
48 = (14 - h)h
48 = 14h - h²
h² - 14h + 48 = 0 Sumados -14 y Multiplicados 48
(h - 8)(h - 6) = 0
h₁ - 8 = 0
h₁ = 8
b₁ = 14 - h
b₁ = 14 - 8
b₁ = 6
h₂ - 6 = 0
h₂ = 6
b₂ = 14 - h
b2 = 14 - 6
b₂ = 8
marcoormeno5:
hubieras aparecido antes
Preguntas similares
hace 10 meses
hace 10 meses
hace 10 meses
hace 4 años
hace 4 años
hace 7 años